Effect of sodium benzoate on Lemon Grass (Cymbopogon citratus) ice tea - Masood, Shahid; Khan, F; Nisa, Alim Un; Ashraf, M; Saeed, A (Bangladesh Journal of Scientific and Industrial Research, 2024)
Sodium benzoate is commonly used as a food preservative to prevent deterioration. According to USEPA standards, the allowable maximum for sodium benzoate in beverages is 0.15%, and 0.13% in fruit juice. A high sodium benzoate intake can induce a variety of illnesses in humans. The current study analyzes the influence of various sodium benzoate concentrations on final product quality. The product was tested to evaluate its physiochemical, proximate, and sensory properties. Acidity, pH, specific gravity, and antioxidant characteristics were identified. The product with the least amount of Na-benzoate performed better than the products with a higher amount of sodium benzoate. Products with 0.06 and 0.07% sodium benzoate were disliked due to a pungent aftertaste, whereas products with 0.05% sodium benzoate were preferred. In terms of physicochemical parameters, all treatments had similar brix, pH, acidity, specific gravity, and antioxidant values. The proximate analyses were also found same for all three treatments. Bangladesh J. Sci. Ind. Res. 59(2), 123-128, 2024